METHODOLOGY OF TEACHING SEMANTIC TYPES OF NOUNS IN ENGLISH IN SECONDARY SCHOOLS - Tursunova , Shakhrinoz Matniyoz qizi (INTERNATIONAL CONFERENCES, 2023)
This article provides information about the methodology of teaching semantic types of nouns in English in general education schools, and about noun vocabulary.